The Lost Ones - DeStefano, Lauren (Los Angeles ; New York ; Disney Press, 2024)
Twins James and Marlene have always felt out of place in their humdrum fishing village, longing to escape the quiet lives their parents envision for them. When Marlene's birthday wish transports them both to an unsettling, magical paradise called Never Land, they discover an unexpected alternative: the chance to stay forever with the charismatic Peter and his Lost Boys. But when their actions reignite a conflict between the fractured Lost Boys, James and Marlene find themselves at odds for the first time in their lives.
Keywords: Hook, -- Captain (Fictitious character) -- Juvenile fiction; Peter Pan -- (Fictitious character) -- Juvenile fiction; Hook, -- Captain (Fictitious character) -- Fiction; Peter Pan -- (Fictitious character) -- Fiction; Never-Never Land (Imaginary place) -- Juvenile fiction; Twins -- Juvenile fiction; Wishes -- Juvenile fiction; Interpersonal conflict -- Juvenile fiction; Never-Never Land (Imaginary place) -- Fiction; Twins -- Fiction; Pays Imaginaire (Lieu imaginaire) -- Romans, nouvelles, etc. pour la jeunesse; Souhaits -- Romans, nouvelles, etc. pour la jeunesse; Conflit interpersonnel -- Romans, nouvelles, etc. pour la jeunesse; Young adult fiction; Fantasy fiction; Fantasy fiction; Action and adventure fiction; Adaptations